2012
DOI: 10.1270/jsbbs.62.303
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of agronomic traits in Tartary buckwheat (<i>Fagopyrum tataricum</i> (L.) Gaertn.)

Abstract: The consumption of products made from Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) has increased in recent years in Japan. Increased consumer demand has led to recognition of the need for early varieties of this crop with high and stable yields. In order to accomplish this, more information is needed on the genetic mechanisms affecting earliness and yield. We conducted genetic analysis of 3 agronomic traits (days to flowering, plant height and total seed weight per plant) to segregate F 2 and F 3 popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
4
8
0
Order By: Relevance
“…This could be due to the early transition from vegetative growth to reproductive development, which is characterized by less vegetative growth. In agreement, Li et al (2012) found that late flowering was associated with increased plant height and higher yields. We also detected negative and non-significant correlations between the number of days to flowering and rutin and quercetin content.…”
Section: Correlation Analysissupporting
confidence: 63%
“…This could be due to the early transition from vegetative growth to reproductive development, which is characterized by less vegetative growth. In agreement, Li et al (2012) found that late flowering was associated with increased plant height and higher yields. We also detected negative and non-significant correlations between the number of days to flowering and rutin and quercetin content.…”
Section: Correlation Analysissupporting
confidence: 63%
“…Study regions were selected on the basis of the literature as either within the region encompassing the place of origin of buckwheat [32], maintaining diverse buckwheat genetic resources [33], and/or having expansive areas of buckwheat cultivation [34]. Study sites were further selected to encompass the range of agroclimatic conditions where buckwheat grows in the Himalayas.…”
Section: Study Sitesmentioning
confidence: 99%
“…is becoming highly attractive because of the high-quality proteins and pharmaceutical ingredients, such as rutin, quercetin and isoquercetin in the seeds [ 25 ]. In China, tartary buckwheat is mainly distributed in the marginal land of Sichuan province, Guizhou province and Yunnan province as the main food of the minorities [ 26 ]. However, in recent years, owing to water deficit and irrational irrigation in these arid areas, soil salinization has become a growing obstacle for tartary buckwheat planting.…”
Section: Introductionmentioning
confidence: 99%